Answer:
y = 17 / 11
Step-by-step explanation:
Equation: −3(4y−7)−y=−2(y−2)
Directions: Solve for 'y' and check
Step 1: Simplify both sides of the equation
−3(4y-7)−y=−2(y−2)
(−3)(4y)+(−3)(−7)+−y=(−2)(y)+(−2)(−2) (Distribute)
−12y+21+−y=−2y+4
(−12y+−y)+(21)=−2y+4 (Combine Like Terms)
−13y+21=−2y+4
−13y+21=−2y+4
Step 2: Add 2y to both sides
−13y+21+2y=−2y+4+2y
−11y+21=4
Step 3: Subtract 21 from both sides
−11y+21−21=4−21
−11y=−17
Step 4: Divide both sides by -11
-11y/-11=-17/-11
y = 17 / 11
Check:
−3(4·17/11−7)−17/11=−2(17/11−2)
−3(4·17/11−7)−17/11 = 10/11
−2(17/11−2) = 10/11
10/11 = 10/11